Modern family capitalism in South Korea - Kwon, Jaok (Global economic elites and the new spirit of capitalism, 2024)
This chapter maintains that despite the infusion of neoliberal management practices post the 1997-1998 Asian financial crisis, family capitalism remains entrenched in South Korea. A life-course analysis of Korean managers highlights a growing number with economic backgrounds, though engineering-trained individuals still dominate top managerial roles. While there’s an uptick in CEOs holding international or MBA degrees, this hasn’t spurred significant external labor market expansion. Examining financial market orientation, leadership, and life conduct, the chapter reveals Korean top managers diverge from neoliberalism. Influenced by the 1997-1998 financial crisis, their financial market orientation does not prioritize shareholder profit maximization in family-owned enterprises. Patriarchal leadership persists, likely rooted in family ownership, and neoliberal ideas are rejected in life conduct. Despite shifts among young managers, a predominant change in family-oriented mindset is not observed. In synthesizing the notion of a global management elite, Korean managers’ data suggests a notable departure from neoliberalism, despite indications of high internationalization in their educational backgrounds.